Scale dependency of pore space topology and transport properties of sandstone CT-scans - Bazaikin, Y.; Gurevich, B.; Khachkova, T.; Kolyukhin, D.; Lebedev, Maxim; Lisitsa, V.; Reshetova, G.; Tcheverda, V. (2016)
© 2016 SEG.Typically the resolution of micro-CT scans of the rock samples and the physical size of the studied volume are linearly connected; i.e. improvement in the resolution requires the sample size reduction. In this paper we consider four images of the Bentheimer outcrop sandstone sample acquired with different resolution to determine the effect of the image scale on the geometrical, topological, and transport properties of the digital core sample. To overcome the strict restriction on the sample size and to approach the representative volumes we suggest using statistical modelling of the images using truncated Gaussian simulation method. This approach preserves total porosity of the sample and reciprocal pore-to-core distribution, however it does not preserve advanced geometrical and topological properties of the pore space such as Minkowski functionals values and Betti numbers of the pore spaces. Nevertheless, permeability and tortuosity of the original images are well matched by synthetic images.